A new species of the extant genus Bulasconotus from mid-Cretaceous Kachin amber (Coleoptera: Zopheridae: Colydiinae) - Li, Yan-Da; Jin, Zhen-Yu; Ślipiński, Adam; Huang, Di-Ying; Cai, Chen-Yang (Papéis Avulsos de Zoologia, 2024)
A fossil species of the extant colydiine genus Bulasconotus Ślipiński & Lawrence, B. carinisternus Li, Ślipiński & Cai sp. nov., is reported from mid-Cretaceous Kachin amber of northern Myanmar. The new species shares with extant Bulasconotus the 3-segmented antennal club, externally open procoxal cavities, and similar sculpture on the pronotum and elytra, but could be recognized by the medially carinated prosternal process. The present discovery provides a valuable example of morphological stasis in the cylindrical bark beetles.